Chronic intertrigo masking inverse psoriasis in an elderly female - Aida Oulehri; Zakia Douhi; Sara Elloudi; Hanane Baybay; Fatima Zahra Mernissi (Our Dermatology Online, 2022)
Psoriasis is a chronic skin disorder that affects up to 5% of patients worldwide. The most common form of psoriasis is the chronic plaque type. Inverse psoriasis (IP) is characterized by its localization on inverse, intertriginous, or flexural body sites and is not always clinically obvious as the lesions usually lack the scale characteristic for typical psoriasis lesions, instead appearing smooth and shiny due to environmental factors. This clinical form is seen mostly in infants. In adults, it is much less frequent and has been suggested to be an indicator of an HIV infection. We report the case of a seventy-year-old female diagnosed with inverse psoriasis based on clinical and dermoscopic criteria. An assessment of the associations revealed no comorbidities.